The genome of Blue-Capped Cordon-Bleu uncovers hidden diversity of LTR retrotransposons in Zebra Finch - Boman, Jesper (MDPI, 2019)
Avian genomes have perplexed researchers by being conservative in both size and rearrangements, while simultaneously holding the blueprints for a massive species radiation during the last 65 million years (My). Transposable elements (TEs) in bird genomes are relatively scarce but have been implicated as important hotspots for chromosomal inversions. In zebra finch (Taeniopygia guttata), long terminal repeat (LTR) retrotransposons have proliferated and are positively associated with chromosomal breakpoint regions. Here, we present the genome, karyotype and transposons of blue-capped cordon-bleu (Uraeginthus cyanocephalus), an African songbird that diverged from zebra finch at the root of estrildid finches 10 million years ago (Mya). This constitutes the third linked-read sequenced genome assembly and fourth in-depth curated TE library of any bird. Exploration of TE diversity on this brief evolutionary timescale constitutes a considerable increase in resolution for avian TE biology and allowed us to uncover 4.5 Mb more LTR retrotransposons in the zebra finch genome. In blue-capped cordon-bleu, we likewise observed a recent LTR accumulation indicating that this is a shared feature of Estrildidae. Curiously, we discovered 25 new endogenous retrovirus-like LTR retrotransposon families of which at least 21 are present in zebra finch but were previously undiscovered. This highlights the importance of studying close relatives of model organisms.